Analisis Yuridis Pandangan Hakim Pengadilan Agama Sukoharjo Terhadap Pelaksanaan Putusan Tuntutan Nafkah Pasca Cerai - Adnya, Salsabeela; Musarrofa, Ita (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2017)
The application of divorce granted by the Religious Court in its verdict will result in legal consequences, ie the ex-wife is entitled to get mut’ah and post-divorce living (except for the ex-wife before conducting sexual intercourse). But, the fact is not always like that. Without legal awareness from the ex-husband, legal certainty for the ex-wife will not be realized and hindered in the effort to get her rights, in the form of mut'ah and post-divorce living. The effectiveness of the execution of the verdict is also influenced by the active role of the judge ordering the ex-husband to provide his ex-wife before the vow of the divorce is read. Although there are not laws governing it, but the Judges of the Religious Court of Sukoharjo conducted legal discovery in accordance with the principles of civil procedure law. The solution to the payment of subsistence payment before being read by the pledge of divorce is a manifestation of legal certainty as stipulated in Article 5 paragraph (1) of Law Number 48 Year 2009 on judicial power. The judge should maximize the role to advise the ex-husband so that his willingness to carry out the contents of the verdict and postpone the reading of the pledge of divorce before the ex-husband fulfills the decision (paying post-divorce living). [Permohonan cerai talak yang dikabulkan Pengadilan Agama dalam amar putusannya akan menimbulkan konsekuensi hukum, yakni mantan isteri berhak mendapatkan mut’ah dan nafkah pasca cerai (kecuali, bagi mantan isteri yang qabla al dukhul). Namun kenyataannya, tidak selalu akibat hukum tersebut (isi putusan berupa kewajiban pemberian nafkah pasca cerai) dilaksanakan oleh mantan suami. Tanpa adanya kesadaran hukum dari mantan suami, kepastian hukum bagi mantan isteri tidak akan terwujud dan terhalang dalam usaha mendapatkan hak-haknya, berupa mut’ah dan nafkah pasca cerai. Efektivitas pelaksanaan putusan juga dipengaruhi oleh peran aktif hakim yang memerintahkan mantan suami untuk memberikan nafkah mantan istri sebelum ikrar talak dibacakan. Meski tidak ada undang-undang yang mengatur, tetapi Hakim Pengadilan Agama Sukoharjo melakukan penemuan hukum yang sesuai dengan asas asas hukum acara perdata. Solusi pembebanan pembayaran nafkah sebelum dibacakan ikrar talak merupakan perwujudan dari kepastian hukum sebagaimana yang diatur dalam Pasal 5 ayat (1) Undang-Undang Nomor 48 Tahun 2009 Tentang Kekuasaan Kehakiman. Hakim seharusnya memaksimalkan peran untuk menasehati mantan suami agar dengan kerelaan hatinya melaksanakan isi putusan dan menunda pembacaan ikrar talak sebelum mantan suami memenuhi isi putusan (membayarkan mut’ah nafkah pasca cerai).]